RETRACTION: Tanggungjawab Eksploitasi Bahan Galian C di Negeri Haya Kecamatan Tehoru Kabupaten Maluku Tengah - Samalehu, Rosmala (PATTIMURA Law Study Review, 2023)
Indonesia is a country rich in minerals. Managing mining businesses and products in Indonesia has been regulated in national laws and regulations, including Law Number 4 of 2009 concerning Mineral and Coal Mining, Law No. 32 of 2009 concerning Environmental Management and Law Number 27 of 2012 concerning Permits Environment. The method used in this research is normative juridical using a statutory and regulatory approach as well as a conceptual approach. The sources of legal materials used in this research are primary legal materials, secondary legal materials and tertiary legal materials. Based on the research results it was found that PT. Waragonda Mineral Pratama in carrying out mining activities for C minerals must comply with statutory regulations Number 23 of 2014 concerning Regional Government, where the Regional Government is the governor, regent/mayor, and apparatus of service heads, service heads, agency heads, work units in the local government environment which is day-to-day controlled by the local government. Form of legal responsibility from PT. Waragonda Mineral Pratama is administrative responsibility and civil liability. Administrative accountability is in the form of building taulid around the coast, and civil accountability is in the form of obligations to fulfill achievements (obligations) and the loss of a legal situation, which is followed by the creation of a new legal situation. In Article 1365 of the Civil Code, it is explained that every act that violates the law and causes loss to another person, requires the person who caused the loss through his fault to compensate for the loss.